(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
Despite the passing of sexual discrimination legislation, the difficulty of combining work and motherhood repeatedly hits the headlines. This paper looks at the American media phenomenon known as the ‘mommy wars’ and asks if British mothers can expect to face the same issues and attitudes as their American sisters.